Origin and evolutionary history of freshwater Rhodophyta: further insights based on phylogenomic evidence - Fangru Nan (Nature Portfolio, 2017)
Abstract Freshwater representatives of Rhodophyta were sampled and the complete chloroplast and mitochondrial genomes were determined. Characteristics of the chloroplast and mitochondrial genomes were analyzed and phylogenetic relationship of marine and freshwater Rhodophyta were reconstructed based on the organelle genomes. The freshwater member Compsopogon caeruleus was determined for the largest chloroplast genome among multicellular Rhodophyta up to now. Expansion and subsequent reduction of both the genome size and GC content were observed in the Rhodophyta except for the freshwater Compsopogon caeruleus. It was inferred that the freshwater members of Rhodophyta occurred through diverse origins based on evidence of genome size, GC-content, phylogenomic analysis and divergence time estimation. The freshwater species Compsopogon caeruleus and Hildenbrandia rivularis originated and evolved independently at the inland water, whereas the Bangia atropurpurea, Batrachospermum arcuatum and Thorea hispida are derived from the marine relatives. The typical freshwater representatives Thoreales and Batrachospermales are probably derived from the marine relative Palmaria palmata at approximately 415–484 MYA. The origin and evolutionary history of freshwater Rhodophyta needs to be testified with more organelle genome sequences and wider global sampling.